Examining the Risk of Delirium Among Residents with Diabetes in Long-Term Care Homes Across Ontario - Heale, Roberta; Gorham, Robyn; Rietze, Lori; Hill, Laura (European Scientific Journal, ESJ, 2025)
Aim: To examine risk factors for delirium in residents with diabetes in Ontario’s LTC homes. Scope: Residents in long-term care (LTC) are vulnerable to negative outcomes related to diabetes, including delirium. Understanding factors related to the risk of delirium for residents with diabetes provides the foundation for the mitigation of delirium in this population. Methods: A population-based retrospective analysis of the RAI-MDS dataset (2019–2020) was conducted. Findings: Diabetes was associated with a statistically significant increased risk of delirium (Odds Ratio: 1.073, CI 1.038–1.109), compounded by polypharmacy. Conclusions: Comprehensive delirium mitigation strategies are needed for this vulnerable population. Strategies to mitigate delirium in this population should be implemented.